Visitantes indesejados : os pedidos de extradição de Franz Stange e Gustav Wagner em uma análise histórico jurídica - Abal, Felipe Cittolin (2012)
This work focuses on the study about two Nazi criminals found in Brazil: Franz Stangl and Gustav Wagner, with the will to research who this Nazis were, which crimes they commited e how they arrived in Brazil, besides analyzing the extradition processes against them and in what way impacted on the press of the southeast region of Brazil the discovery of this Nazis in Brazil and the results of the extradition processes. Stangl was Commander of Sobibor and Treblinka death camps, and also worked in the euthanasia institute of Hartheim, and participated actively on the murder of thousands of persons, specially Jews. Wagner, that also had worked in Hartheim, was second in charge on Sobibor death camp, being known for his cruelty and having assassinated personally dozens of persons of Hebrew origin. Both, after the war, escaped from Europe with the aid of members of the catholic church and, after a period in East Asia, they fleed to Brazil. Stangl was found in the country in 1967 and suffered extradition requests from the Federal Republic of Germany, Austria, and Poland, and, after the trial of this requests by the Brazilian Supreme Court, the Nazi was turned over to Germany. Wagner was found in Brazil eleven years after and also had his extradition requested by the Federal Republic of Germany, Austria, Poland and Israel. The understanding of the Brazilian Supreme Court on the Wagner case, however, was different, being that the extradition of the Nazi was denied. The research concentrated, in a first moment, in analyzing both the subjects and their crimes, as well as the places where they committed the felonies that they were charged to, after, describe how the Nazis were found in Brazil and the impact of these facts in the newspapers from the southeast region of Brazil, being able to, at this moment, start to study the treatment given to the institute of extradition on the Brazilian laws of the time of the judgments, the processes and their results, ending with an analysis about the repercussion of the results of the trials in the newspapers from São Paulo and Rio de Janeiro. In the execution of the research were utilized specific bibliography, interviews with survivors from Sobibor and Treblinka death camps, the extradition processes and newspapers of the time. This steps were made to solve the main problem of the research: What were the legal reasons that based the different results on both trials on that historical moment in front of the apparent equality of the cases? It came to the conclusion that this happened because of the strictly legalist analysis made by the Brazilian Supreme Court in the Wagner case, despite the international laws against criminals that participated in genocide and justice itself.